2018
DOI: 10.3389/fphys.2018.01768
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo dsRNA Cleavage Has Sequence Preference in Insects

Abstract: Exogenous dsRNA enters the insect body and can induce the RNAi effect only when it is cleaved into siRNA. However, what kinds of base composition are easier to cut and what kinds of siRNA will be produced in vivo is largely unknown. In this study, we found that dsRNA processing into siRNA has sequence preference and regularity in insects. We injected 0.04 mg/g dsRNA into Asian corn borers or cotton bollworms according to their body weight, and then the siRNAs produced in vivo were analyzed by RNA-Seq. We disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…The mechanisms that cause the variability in the sensitivity of different portions of a target gene to RNAi are not entirely clear. However, in some insects, researchers have shown that cleavage of dsRNAs can be affected by their sequence 25 . In Asian corn borer ( Ostrinia furnacalis ) and cotton bollworm ( Helicoverpa armigera ), injected dsRNAs tended to produce siRNAs specifically cut at GGU nucleotide sequences, and dicing was reduced if these consensus sites were removed 25 .…”
Section: Strategies For Enhancing Rnai Efficiencymentioning
confidence: 99%
“…The mechanisms that cause the variability in the sensitivity of different portions of a target gene to RNAi are not entirely clear. However, in some insects, researchers have shown that cleavage of dsRNAs can be affected by their sequence 25 . In Asian corn borer ( Ostrinia furnacalis ) and cotton bollworm ( Helicoverpa armigera ), injected dsRNAs tended to produce siRNAs specifically cut at GGU nucleotide sequences, and dicing was reduced if these consensus sites were removed 25 .…”
Section: Strategies For Enhancing Rnai Efficiencymentioning
confidence: 99%
“…This knowledge might be useful to predict functional siRNA fragments that result from a specific dsRNA sequence. Thus, we can achieve higher RNAi effects by incorporating these sites into dsRNA …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Thus, we can achieve higher RNAi effects by incorporating these sites into dsRNA. 123,124 Length of dsRNA: Natural uptake of dsRNAs is length dependent and researchers have tested dsRNA molecules ranging from 50 bp to 2000 bp, which generates around 10-25 siRNA fragments after Dicer processing. However, 200-550 bp are more effective in triggering RNAi effects.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, RNAi efficiency is relatively low in lepidopteran insects and this is a core factor that frustrates the application of this technology (Terenius et al, 2011; Cooper et al, 2019). Many factors affect RNAi efficiency in insects, including the absence of RNA-dependent RNA polymerase (RdRP)-mediated synthesis of secondary small interfering RNAs (siRNAs) (Sijen et al, 2001), the rate of dsRNA processing into siRNAs (Guan et al, 2018a), the dsRNA uptake and transport mechanism (Luo et al, 2012), and the degradation rate of dsRNA (Christiaens et al, 2014; Spit et al, 2017; Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%